Settlers, traders, and trails - Uhl, Xina M. (Westward expansion: America's push to the Pacific., 2018)
Explores the history of the expansion of the American West including the pioneers who traveled by wagon trains and the traders who made their living in the new land. Includes resources for further research and a glossary.